Towards a Minimum Viable Product for Environmental Management System: A Case Study - Ribeiro, Rafael; Bernardino, Maicon; Clemente, Willian; Nogueira, Iago; Rodrigues, Elder; Basso, Fabio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Environmental consulting firms operate in a dynamic landscape, managing diverse clients and projects. The substantial volume of data handled in this domain necessitates effective management tools to ensure efficiency and accuracy. Problem: Despite the complexity of environmental management tasks, there is a notable absence of specialized tools tailored to this industry. This deficiency leads to data loss and system malfunctions, undermining the effectiveness of environmental consulting operations. Solution: This study addresses the identified gap by developing a Minimum Viable Product (MVP) for an environmental management system. Through iterative design and testing phases, a case study is presented, illustrating the refinement process that led to the creation of a stable MVP. Theory of SI: The project is grounded in Soft Systems Methodology (SSM), providing a structured approach to address complex, real-world problems within the environmental consulting domain. Summary of Results: Rigorous testing and evaluation of the MVP demonstrated its efficacy and suitability for industrial deployment. The results endorse its implementation as a viable solution for enhancing team productivity and facilitating efficient information management within environmental consulting firms. Moreover, the system’s capacity to mitigate delays in legal compliance activities underscores its potential to streamline environmental management practices. Contributions and Impact in the IS Area: Through the case study, this research showcases the tangible benefits of the developed system, including improved task performance, enhanced data management capabilities, and timely regulatory compliance. These findings indicate significant market potential for the system, positioning it as a valuable asset for the evolution of environmental consulting practices.